Infectious endophthalmitis associated with umbilical infection in Japanese black calf: a case report - Sato, Reiichiro; Iguchi, Atsushi; Uemura, Ryoko; Tsujita, Hiroki; Steiner, Adrian (Frontiers in Veterinary Science, 2025)
A 3-day-old Japanese black calf presented with a swollen and tender umbilical cord and diffusely cloudy and keratoconus eyes. Abdominal ultrasonography confirmed mild enlargement of both umbilical arteries and the urachus with a hyperechoic lumen. Additionally, a hyperechogenic structure suggestive of pus was noted near the abdominal wall. Fluorescein staining revealed corneal epithelial injury, whereas slit lamp examination identified corneal edema, increased corneal thickness, and keratitis with vascularization of the corneal stroma. Based on these findings, diagnoses of omphaloarteritis, omphalourachitis, and bullous keratitis were made. Both umbilical arteries and the urachus were surgically removed; both ocular globes were covered with a third eyelid flap, which was released 30 days postoperatively. On the follow-up, ocular ultrasonography indicated bleeding or fibrin deposits in the vitreous body of the right ocular globe. Because intraocular inflammation was suspected, anterior aqueous humor was collected from the right ocular globe, and bacterial examination was performed with the umbilical artery abscess, urachal abscess, and intraabdominal pus collected intraoperatively. Escherichia coli was isolated from the umbilical artery abscess, urachal abscess, intraabdominal pus, and aqueous humor, and all isolates exhibited identical genotypes. These findings suggest that endophthalmitis occurred as a result of the hematogenous spread of bacteria originating from septic umbilical cord remnants and that ocular ultrasonography is useful for assessing intraocular pathologies.